2015
DOI: 10.1016/j.biologicals.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The importance of formulation in the successful lyophilization of influenza reference materials

Abstract: Lyophilized Influenza antigen reference reagents are a critical resource in the quality control of influenza vaccines. A standard formulation has been used successfully at NIBSC for many years however, following the unexpected occurrence of a collapsed appearance in a particular batch a study was carried out to establish the impact of the sugar concentration in the formulation using modulated differential scanning calorimetry (mDSC) and nuclear magnetic resonance spectroscopy (NMR). There was a correlation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…This result complements our earlier finding ( Duru et al, 2015 ), which showed that for freeze-dried influenza antigen reference preparations, NaCl crystallization was a critical factor—an increase in the amorphous content using raised levels of sucrose (above 1.4% w/w) resulted in a collapsed freeze-dried appearance. From the mDSC, it was concluded that raising the sucrose content (although usually a desirable stabilizer for freeze drying), resulted in inhibition of the crystallization of the NaCl co-formulant and that this crystallization was critical in producing an acceptable freeze-dried appearance.…”
Section: Discussionsupporting
confidence: 90%
“…This result complements our earlier finding ( Duru et al, 2015 ), which showed that for freeze-dried influenza antigen reference preparations, NaCl crystallization was a critical factor—an increase in the amorphous content using raised levels of sucrose (above 1.4% w/w) resulted in a collapsed freeze-dried appearance. From the mDSC, it was concluded that raising the sucrose content (although usually a desirable stabilizer for freeze drying), resulted in inhibition of the crystallization of the NaCl co-formulant and that this crystallization was critical in producing an acceptable freeze-dried appearance.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, mDSC is particularly useful for detecting T g present with other overlapping thermal events (glass transition) [131]. Therefore, mDSC is particularly useful for detecting T g present with other overlapping thermal events (glass transition) [132], to correlate eutectic temperature (lowest possible melting temperature over all of the mixing ratios for the involved component species) events leading to cake collapse [133] and to study the effects of annealing on the thermal properties of frozen sucrose solutions [134][135][136]. It was also used as an additional method to ssHDX-MS for the analysis of the conformation of lyophilized IgG1 (Table 2) [137].…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…‘Reversing’ and ‘non-reversing’ heat flow components do not refer to the reversible or irreversible nature of events; they refer to the heat capacity component and time-dependent kinetic component of total heat flow, respectively. MDSC has been used to determine Tg values for systems with small changes in heat capacity [48], to correlate eutectic temperature events to cake collapse [53] and to study the effects of annealing on the thermal properties of frozen sucrose solutions [54]. …”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%